2015
DOI: 10.1208/s12248-015-9787-8
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Considerations for Approval of Generic Inhalation Drug Products in the US, EU, Brazil, China, and India

Abstract: Abstract. This article describes regulatory approaches for approval of Bgeneric^orally inhaled drug products (OIDPs) in the United States, European Union, Brazil, China and India. While registration of a generic OIDP in any given market may require some documentation of the formulation and device similarity to the Boriginal^product as well as comparative testing of in vitro characteristics and in vivo performance, the specific documentation approaches, tests and acceptance criteria vary by the country. This di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 37 publications
(33 reference statements)
0
25
0
1
Order By: Relevance
“…Current bioequivalence guidance requires that a test product match C max and AUC 0– t of the reference product to conclude bioequivalence . When gastrointestinal absorption contributes to exposure, equivalent efficacy may be concluded by assessing lung deposition using C max or AUC 0–0.5h where lung dose is assessed in a charcoal block study, and equivalent safety may be concluded in a study without charcoal block, as the evaluation of safety requires assessment of exposure resulting from both pulmonary and gastrointestinal absorption . Therefore, consideration must be given to both lung deposited dose and mouth‐throat dose during product development.…”
Section: Discussionmentioning
confidence: 99%
“…Current bioequivalence guidance requires that a test product match C max and AUC 0– t of the reference product to conclude bioequivalence . When gastrointestinal absorption contributes to exposure, equivalent efficacy may be concluded by assessing lung deposition using C max or AUC 0–0.5h where lung dose is assessed in a charcoal block study, and equivalent safety may be concluded in a study without charcoal block, as the evaluation of safety requires assessment of exposure resulting from both pulmonary and gastrointestinal absorption . Therefore, consideration must be given to both lung deposited dose and mouth‐throat dose during product development.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the device aspect of drug–device combination OIDPs, these products are recommended to provide a user interface that is similar to the RLD with similar operating principles to ensure therapeutic equivalence . The formulation for MDIs should be qualitatively and quantitatively the same as the RLD; for DPIs qualitative sameness is required, and if it is not quantitatively the same the differences should be justified with additional data . Taken together, a potential generic OIDP developer has to balance the appropriateness of passing all FDA‐recommended studies, producing a generic drug–device combination product that can be substituted for the RLD without additional training prior to use and/or without the intervention of a healthcare provider and observing any existing device patents that may exist.…”
Section: Status Of Generic Orally Inhaled Drug Products In the Unitedmentioning
confidence: 99%
“…8 The formulation for MDIs should be qualitatively and quantitatively the same as the RLD; for DPIs qualitative sameness is required, and if it is not quantitatively the same the differences should be justified with additional data. 9 Taken together, a potential generic OIDP developer has to balance the appropriateness of passing all FDA-recommended studies, producing a generic drug-device combination product that can be substituted for the RLD without additional training prior to use and/or without the intervention of a healthcare provider 10 and observing any existing device patents that may exist. Meeting these standards may require many device or even formulation iterations before generating an approvable product.…”
Section: Status Of Generic Orally Inhaled Drug Products In the Unitedmentioning
confidence: 99%
“…Despite the absence of an FDA guidance document on the BE of OIP in general, scientific and regulatory considerations for demonstrating BE between dry powder inhalers (DPI) have been proposed [20], and recently reviewed [21]. The FDA has developed an aggregate weight-of-evidence approach which utilizes in vitro studies, PK equivalence studies, and pharmacodynamic (PD) or clinical endpoint (CE) studies (also called Therapeutic Equivalence (TE) studies), to establish BE of inhalation products [21].…”
Section: North American Requirements (Fda and Hc)mentioning
confidence: 99%
“…The FDA has developed an aggregate weight-of-evidence approach which utilizes in vitro studies, PK equivalence studies, and pharmacodynamic (PD) or clinical endpoint (CE) studies (also called Therapeutic Equivalence (TE) studies), to establish BE of inhalation products [21]. Equivalence in all categories of interest is required [22].…”
Section: North American Requirements (Fda and Hc)mentioning
confidence: 99%